THE EFFECT OF POPULATION DYNAMICS ON FOREST COVER IN DARO LEBU WEREDA, WEST HARARGHE ZONE, OROMIA REGION, ETHIOPIA - Legese, Delelegy; Roba, Alemayehu Diriba (International Journal of Research -GRANTHAALAYAH, 2021)
Forest is one of renewable land properties which endowed with numerous resources that are valuable to man. The quality of the environment is constantly losing its status due to increase in population size in most countries of the world. The general objective of this study was to assess the effect of population dynamics on forest cover in West Hararghe Zone in general and Daro Labu Wereda (DLW) in particular. Systematic random sampling technique was used to select the target population of this study whose total number was 364 households from four kebeles of DLW. Questionnaire, interview, FGD and satellite imagery used as data gathering tools for this study. The quantitative data of this study were analyzed using descriptive statistics and the qualitative data were discussed and interpreted through narration. As the result in this study a mixed method was used. This study is triangulation study in its design. The study was found out that population dynamics had contributed a lot to deforestation of the wereda under the study through agricultural land expansion, settlement, fuel wood gathering and illegal tree cutting. Thus due to population growth, lack of alternative livelihood approach, ruthless profit making, lack of economic transformation human encroachment and lack of alternative sources of energy. Population growth had contributed greatly to forest deforestation especially as it affected the forest covers. The major findings were observed that expansion for cultivated and settlement LULC classes rapidly increased from1973 to 2013 on the contrary forest and shrub lands decreased in DLW due to population dynamics and human encroachment in the forest cover. Therefore, there is an urgent need with government for the various stakeholders in environmental resource management to provide mechanism that can prevent the forest cover from further reduction in the study area.